Exometabolites of endospore-forming bacteria of Bacillus genus identified by genomic-metabolomic profiling - А. M. Ostapchuk; М. D. Shtenikov; V. О. Ivanytsia (The Ukrainian Biochemical Journal, 2020)
The set of unique bioactive metabolites produced by marine bacilli is already known but the metabolomic of these bacteria is underinvestigated. The aim of this work was to carry out the comparative analysis of metabolomic and genomic traits of Bacillus velezensis ONU 553, Bacillus pumilus ONU 554, Bacillus subtilis ONU 559 strains isolated from Black Sea bottom sediments. Organic extracts of each strain were analyzed using high-resolution liquid chromatography-mass spectrometry. General annotation of genomes was performed using PATRIC, search for secretory signals in the primary structure of selected proteins with using Signal IP analysis. The search of biosynthetic gene clusters was performed using antiSMASH, PRISM 3 and BiG-SCAPEs, the reconstruction of metabolites- with PRISM 3 and TransATor analyzes. The study allowed to found and identified 90, 33 and 43 metabolites in the strains Bacillus velezensis ONU 553, Bacillus pumilus ONU 554 and Bacillus subtilis ONU 559 respectively. The compounds found in metabolome were subdivided into two groups: those which are known members of the genus Bacillus and those new to both genus and prokaryotes in general. Among the secondary metabolites of studied strains the variants of the nonribosomal peptide class surfactins (anhteisoC16-surfactin, surfactin B2-me ester), gageostatins, fengycins and amicoumacins, and the secreted protease inhibiting pentapeptide GPFPI were identified. The biosynthetic clusters of lipopeptides of the pumilacidin subgroup and amicoumacin antibiotic AI-77A were identified for the first time with the use of bioinformatic tools. The data obtained replenish the understanding of the marine bacilli biosynthetic potential.